L’effetto degli stili decisionali e dell’ansia genitoriale sulla percezione delle paure infantili: uno studio pilota - Martina Messina; Rossella De Falco; Genoveffa Amore; Teresa Capparelli; Silvia Dell'Orco; Carmen Giannetti; Claudia Langella; Benedetta Muzii; Rita Scognamiglio; Tilde Annunziato (Phenomena Journal)
Background. Emotional experiences are essential for  psychophysical development of children. Many factors are involved in this process: socio-cultural environment, relationships, parental behaviour and  more. Caregivers play a crucial role in the development process of their children, as much as their ability to make a choice and to deal with children’s emotions [15]. A detailed review of relevant scientific literature reveals a research gap in the field of children’s fears, compared to parental anxiety and decision-making styles. This gap needs to be tackled in order to improve understanding of childhood fears. Aims. The pilot study investigate the correlation between caregivers’ trait anxiety and decision-making styles, to explore in depth their perception of children fears. Methods. Sample includes parents of three-to-ten-year-old children (n = 288), both mothers and fathers. Participants submitted online replies to three psychological tools: General Decision Making Style (GDSM), State-Trait Anxiety Inventory – Y Form (STAI-Y), Fear Survey for Children Revised – Parents Version (FSSCR-P). Results. Statistical analyses show a significant correlation between Trait Anxiety and Dependent decision-making style (r = .347). Statistically significant correlation was also noted between Trait Anxiety and Avoidant decision-making style (r = .373). Furthermore, anxiety can affect parents perception of children fear of unknown (F(1,25) = 9,22; p < .05) and it is predictive (β = .185; p < .05) of parents perception of children fear of failure and criticism. Then, Dependent decision-making style is predictive (β = .18; p <.05) of parental perception of children fear of abandonment. Conclusions. Looking at the family system and parental relationships represents an essential step for research in the field of development psychology, in order to understand childhood fears. Future studies need to involve a wider sample, including both caregivers and children. Finally, testing new hypothesis could lead to new psychotherapeutic treatment and experience in the perspective of integrated Gestalt therapy.